Wyznawcy wiary politycznej w literaturze. Lidia Czukowska Opustoszały dom i Jelena Ginzburg Stroma trasa - Piertrzycka-Bohosiewicz, Krystyna (Przegląd Rusycystyczny, 2006)
ПРИВЕРЖЕНЦЫ ПОЛИТИЧЕСКОЙ ВЕРЫ В ХУДОЖЕСТВЕННОЙ ЛИТЕРАТУРЕ. ЛИДИЯ ЧУКОВСКАЯ ОПУСТЕЛЫЙ ДОМ И ЕЛЕНА ГИНЗБУРГ КРУТОЙ МАРШРУТ Резюме Тоталитаризм ХХ столетия обладает всеми атрибутами религии (обожествление власти, партии, вождей, доктрины), наличие ритуала, ортодоксии и ереси. Наиболее развитый сталинский вариант светской религии стремится найти ответ на универсальные вопросы бытия и покорить душу человека. FOLLOWERS OF POLITICAL BELIEF IN LITERATURE.(LIDIA CZUKOWSKA OPUSTELYI DOM AND JELENA GINZBURG KRUTOI MARSHRUT) Summary All the religious attributes (divinization of authorities, party, leaders, doctrine), presence of rituals, orthodoxy and heresy are characteristic of totalitarianism of the 20th century. The most developed Stalinist variant of secular (political) religion had an ambition to fi nd the solution to all universal existential problems, attempting at the same time to take control of the human soul.